Temporal dynamics of sexual dimorphism in a dioecious species - Moquet, L (Ann Bot, 2020)
BACKGROUND AND AIMS: Sexual dimorphism for floral traits is common in dioecious plant species. Beyond its significance for understanding how selection acts on plant traits through male vs. female reproductive function, sexual dimorphism has also been proposed as a possible risky characteristic for insect-pollinated plants, as it could drive pollinators to forage mostly on male plants. However, even though most flowering plant species spread their flowering across several weeks or months, the temporal variation of floral phenotypes and sexual dimorphism have rarely been investigated. METHODS: We performed a survey of male and female plants from the dioecious generalist-pollinated Silene dioica (Caryophyllaceae) in a common garden experiment, over two consecutive flowering seasons. Flower number and floral size were measured each week, as well as pollen quantity and viability in male plants. KEY RESULTS: Sexual dimorphism was found for all investigated floral traits, with males showing an overall higher investment in flower production and flower size. Males and females showed a similar temporal decline in flower size. The temporal dynamics of daily flower number differed between sexes, with males showing a peak in the middle of their flowering season, whereas flower production by females was quite stable over time. At the scale of the experimental population, both individual and floral sex ratios appeared to vary across the flowering season. Moreover, because the onset of flowering varied among plants, the magnitude of sexual dimorphism in floral size also fluctuated strongly through time. CONCLUSIONS: Capturing male/female differences with only one temporal measurement per population may not be informative. This opens stimulating questions about how pollinator behaviour and resulting pollination efficiency may vary across the flowering season.